Urban pedagogy as an educational experience for adults - Barrio de la Puente, José Luis; Fernández-Solis, Jesús Damián (Pulso. Revista de educación, 2007)
The concept of urban pedagogy and educating city are very important in todays society education. Because of that reason theoretical contributions and raised issues of this educational approach are analyzed in this paper. An educational innovative project the pedagogical knapsack for adult education in urban signifi cative learning has been deployed in an educational centre. The pretension is for the grown up pupils to integrate in-class theoretical knowledge from several knowledge fi elds, having as a referent the context and the environment in which he or she inhabits. Following this the project development is described and evaluated, emphasizing the most important activities that were carried out as well as indicating most relevant conclusions from this experience in educational innovation.
Keywords: Project; Innovation; Learning Process; Urban Pedagogy; Educating City